Experiments on electromagnetic interaction of linearly polarized photons with nucleons and nuclei - Gorbenko, V.G.; Kolesnikov, L.Ya. (Вопросы атомной науки и техники, 2003)
Experiments on electromagnetic interaction of nucleons and nuclei with linearly polarized photon beams produced by coherent bremsstrahlung of high energy electrons from diamond single crystal targets are reviewed. The details of experimental equipment, the methods of beam monitoring and photon polarization evaluation, as well as the methods for measuring cross section asymmetries are discussed. The experimental results for polarization parameters of pion photoproduction and photodisintegration reactions are presented and discussed along with theoretical analyses.